Makna Pemberian Remisi kepada Warga Binaan Pemasyarakatan Terpidana Seumur Hidup - Masirri, Jennifer Regina; Bachri, Syamsul; Riza, Marwati (Universitas Negeri Malang, 2022)
This study analyzed the legal position of presidential decrees in granting remissions to inmates and the meaning of giving remissions to lifelong criminal inmates. This study used normative juridical research with a statutory approach, a conceptual approach, and a comparative approach—sources of data obtained from primary and secondary legal materials. The data obtained were analyzed using descriptive methods. The results of the study showed that the legal position of the presidential decree in granting remissions that changed the type of punishment for inmates did not have juridical power. Changes in the type of crime should be carried out in the form of clemency as stipulated in the 1945 Constitution of the Republic of Indonesia. The meaning of giving life imprisonment to prisoners in prison in Indonesia was different from some countries in the world, which only reduced the criminal period and did not change the type of punishment because due to remission, it was excluded from crimes that were very dangerous to the general public.